Legal Protection for Revenge Porn Victims in the Sexual Violence Crime Law (UU No. 12 of 2022) - Yoga Putra Dinantira (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
In recent times, there has been a notable surge in public awareness around a multitude of incidents involving the dissemination of explicit content without consent, often referred to as revenge porn. The issue of addressing a specific category of criminal behavior including sexual assault inside the realm of virtual environments has garnered significant public interest within the nation. On April 14, 2022, the government enacted the TPKS Law with the aim of providing legal safeguards for victims. This study is a qualitative research with a juridical-normative approach, focusing on providing a descriptive analysis of the legal safeguards available to victims of revenge pornography, as outlined in the TPKS Law. The findings of this research demonstrate that the TPKS Law offers a favorable indication for the prevention and management of instances of sexual assault in Indonesia, as it establishes legal clarity, safeguards, and support for victims. Nevertheless, it is important to emphasize that the issue of victimization of individuals often persists as a result of law enforcement officers' limited comprehension of sexual assault.